El Excentrico, 1971-06-20 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
June 5, 1971 [5 de junio de 1971]. No volume or issue number. Cover has the high school graduation announcement, diploma and photograph of El Excetnrico's Social Editor Anthony Marc Garcia